2018
DOI: 10.1177/0300985817754122
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hepatic Fibrosis in a Purebred Spanish Horse Foal: Pathology and Genetic Studies on PKHD1 Gene Mutations

Abstract: A 1-month-old Purebred Spanish Horse (PSH) foal presented with progressive hepatic failure culminating in death. Hepatic lesions were consistent with congenital hepatic fibrosis (CHF). Genetic studies in the PKHD1 gene in the affected foal revealed that it was heterozygous for the 2 previously described single-nucleotide polymorphisms (SNPs) linked to CHF in Swiss Franches-Montagnes (SFM) horses. In addition, 2 novel mutations were detected, the foal being homozygous for one of them and heterozygous for the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Congenital Liver Fibrosis (CLF) is a fatal hepatic disease originally reported in Franches Montagnes horses 69 , and more recently reported in Spanish horses 70 as a Mendelian disease. However, the five reported variants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital Liver Fibrosis (CLF) is a fatal hepatic disease originally reported in Franches Montagnes horses 69 , and more recently reported in Spanish horses 70 as a Mendelian disease. However, the five reported variants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 Congenital hepatic fibrosis has been reported in dogs, cats, calves, horses, and nonhuman primates but to the authors’ knowledge has not been reported in snakes. 5,9,16,25,36 38…”
Section: Discussionmentioning
confidence: 99%
“…5 Congenital hepatic fibrosis has been reported in dogs, cats, calves, horses, and nonhuman primates but to the authors' knowledge has not been reported in snakes. 5,9,16,25,[36][37][38] Historically, DPMs have been misdiagnosed as benign biliary neoplasms, such as biliary adenoma or biliary cystadenoma, because they share histopathologic features: tubules of well-differentiated biliary epithelium supported by moderate amounts of intervening stroma. The difficulty distinguishing DPMs from benign biliary neoplasms has made it difficult to assess the true incidence of the two processes in human and veterinary pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the PKHD1 gene have been reported in horses with congenital hepatic fibrosis (MOLÍN et al, 2018). Most pathogenic PKHD1 variants lead to polycystic kidney and liver defects; however, in some cases, only liver symptoms are observed, as described in horses with a monogenic autosomal recessive inheritance that presents congenital hepatic fibrosis (dRÖGEMÜLLER et al, 2014).…”
mentioning
confidence: 99%